Peran Income Audit Dalam Mengurangi Kesalahan Terhadap Pemeriksaan Pendapatan: Studi Hotel Prama Sanur Beach Bali - I Wayan Sudarsana; Ni Putu Trisna Windika Pratiwi (UNHI Press, 2026)
This study aims to analyze the role of income audit in identifying and reducing revenue recording errors at Hotel Prama Sanur Beach Bali and to determine the factors that hinder its implementation. This research uses a descriptive method with a qualitative approach. The research data were obtained through observation, interviews, and documentation with the main informant being the income auditor, supported by documents such as daily revenue reports and hotel transaction records. Data analysis employed the interactive model of Miles and Huberman, which consists of data reduction, data display, and conclusion drawing. The results show that the main problem in the income audit process is the occurrence of revenue not balance caused by errors in posting room charges, discrepancies in recording Food and Beverage (FB) outlet revenue, errors in recreation revenue, and inaccuracies in the calculation and posting of tax and service charges. These problems are generally triggered by human error, such as incorrect nominal input, incorrect use of account codes, double posting, and delays in posting transactions. Income audit plays a role as an internal control mechanism through a daily verification and reconciliation process that functions as a detective control and corrective control in detecting and correcting revenue recording errors. However, the effectiveness of income audit implementation is still influenced by several obstacles, such as a high level of human error, delays in supporting documents, high transaction volumes during high occupancy periods, suboptimal coordination between departments, and constraints in system usage.